Systemic Lupus Erythematosus and Cardiovascular Disease: A Mendelian Randomization Study - Gao, Ning; Kong, Minjian; Li, Xuebiao; Wei, Dongdong; Zhu, Xian; Hong, Ze; Ni, Ming; Wang, Yifan; Dong, Aiqiang (Frontiers in Immunology, 2022)
Background. Although studies have shown that patients with Systemic Lupus Erythematosus (SLE) have a higher risk of Cardiovascular Disease (CVD), a causal association between genetic susceptibility to SLE and risk of cardiovascular disease has not been reported. Therefore, in this study, we aimed to explore whether there is a causal relationship between SLE and CVD. Methods. Genetic instruments were obtained from genome-wide association studies(GWAS) of SLE and of CVD，respectively. Two-sample Mendelian Randomization (MR) analysis was performed with IVW as the primary method to infer causality. At the same time, a series of repeated analysis, sensitivity analysis, and IVs strength evaluations were carried out to verify the reliability of our results. Results. Mendelian randomized analysis showed that genetic susceptibility to SLE was associated with a higher risk of Heart Failure (HF) (OR=1.025;95%CI, (1.009-1.041), P=0.002), Ischemic Stroke (IS) (OR=1.000;95%CI, (1.000-1.000), P=0.026), and Venous Thromboembolism (VTE) (OR=1.001;95%CI,(1.000-1.002),P=0.026). But the genetic susceptibility to SLE was negatively correlated with the risk of Type 2 Diabetes (T2DM) (OR=0.968;95%CI, (0.947-0.990), P=0.004). Conclusion. Our MR analysis explored the causal association between SLE and CVD, which would help to improve our understanding of the basic disease mechanisms of SLE and provide comprehensive CVD assessment and treatment for SLE patients.